Who rules in science? : an opinionated guide to the wars - Brown, James Robert (Harvard University Press, 2001)
What if something as seemingly academic as the so-called science wars were to determine how we live? This book reveals how little we've understood about the ongoing pitched battles between the sciences and the humanities - and how much may be at stake.